2021
DOI: 10.1186/s12989-020-00394-8
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular health impacts of wildfire smoke exposure

Abstract: In recent years, wildland fires have occurred more frequently and with increased intensity in many fire-prone areas. In addition to the direct life and economic losses attributable to wildfires, the emitted smoke is a major contributor to ambient air pollution, leading to significant public health impacts. Wildfire smoke is a complex mixture of particulate matter (PM), gases such as carbon monoxide, nitrogen oxide, and volatile and semi-volatile organic compounds. PM from wildfire smoke has a high content of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
97
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(119 citation statements)
references
References 170 publications
(161 reference statements)
0
97
1
2
Order By: Relevance
“…Exposure to PM 2.5 , specifically from wildfires, has been associated with negative health outcomes (3,4,(10)(11)(12)(13)(14)(15)(16), including all-cause mortality and respiratory morbidity, as well as asthma, chronic obstructive pulmonary diseases, and others (11,12,17,18). In particular, studies have shown that short-term wildfire-specific PM 2.5 exposure is linked to increases in asthma symptoms, emergency department visits for respiratory symptoms, and respiratory hospital admissions, as well as increases in risk and severity of respiratory viral infections (4,(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to PM 2.5 , specifically from wildfires, has been associated with negative health outcomes (3,4,(10)(11)(12)(13)(14)(15)(16), including all-cause mortality and respiratory morbidity, as well as asthma, chronic obstructive pulmonary diseases, and others (11,12,17,18). In particular, studies have shown that short-term wildfire-specific PM 2.5 exposure is linked to increases in asthma symptoms, emergency department visits for respiratory symptoms, and respiratory hospital admissions, as well as increases in risk and severity of respiratory viral infections (4,(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Base on a study conducted by Hooghiem et al (2020) wildfire outbreaks has been found to emit huge quantity of trace gases and aerosols into the atmosphere. Besides the economic loss potential characterized by wildfire, it is considered as a major source of ambient air pollution resulting to negative impact on public health due to its emitted smoke (Chen, Samet, Bromberg, & Tong, 2021). The impact of wildfire on public health is sometimes felt far beyond it immediate ignition point due to smoke movement (Cascio, 2018;Chen et al, 2021;Le et al, 2014).…”
Section: Biodiversity and Environmental Consequences Of Wildfire Outbreak In Sierra Leonementioning
confidence: 99%
“…Concomitantly, wildfire outbreak has negatively been impacting the socio-economic activities of wildfire prone communities especially in the northern part of Sierra Leone. For example, in Sierra Leone and elsewhere, wildfire burning release Co2 emission and other greenhouse gases into the atmosphere (Awoko, 2016;Chen et al, 2021). Additionally, the inhalation of smoke during burning each season pose a serious health threats to communities prone to frequent fires each year (Awoko, 2016;Chen et al, 2021).…”
Section: Biodiversity and Environmental Consequences Of Wildfire Outbreak In Sierra Leonementioning
confidence: 99%
“…Across both human and animal research, additional data is needed on the effects of natural exposure to wildfire smoke. With the increased occurrence of wildfires, literature studying the impacts of wildfires on human health has been rapidly expanding [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. The evaluation of smoke and particulate matter exposure and human health outcomes has been a particular focus [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%